Erratum to the article "The usefulness of an optical monitor for the assessment of human exposure to fine dust in indoor air" (MED PR. 2019;70(2):213-20) - Małgorzata Kowalska; Anna Mainka; Walter Mucha (Nofer Institute of Occupational Medicine, 2022)
The original version of the article can be found at: https://doi.org/10.13075/mp.5893.00780.